Seroprevalence of Cytomegalovirus, Toxoplasma gondii, Syphilis, and Hepatitis B and C Virus Infections in a Regional Population Seropositive for HIV Infection - Daniel G Johns; M John Gill (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the prevalence of exposure to cytomegalovirus (CMV), Toxoplasma gondii, syphilis, hepatitis B virus (HBV) and hepatitis C virus (HCV) in a large, well characterized, regional population presenting for human immunodeficency virus (HIV) care.